Regional variations of in vivo surface stiffness of soft tissue layers of musculoskeletal extremities. (11th October 2019) - Neumann, Erica E.; Owings, Tammy M.; Erdemir, Ahmet
Abstract: Surface stiffness of bulk soft tissue in musculoskeletal extremities is important to consider in the design of prosthetics, exoskeletons, and protective gear. This knowledge is also foundational for surgical simulation and clinical interventions leveraging manipulation of the musculoskeletal surfaces. Injuries to musculoskeletal extremities are common and surgical and preventive interventions require interactions between various objects such as surgical tools and support surfaces with tissue boundaries. While a handful of investigations examined the variations in indentation mechanics due to pathology or injury specific sites, a comprehensive analysis across the surfaces of musculoskeletal extremities has not been completed. In this study we examine variations of surface stiffness across 8 sites of the upper and lower arms and legs for 95 subjects using an instrumented ultrasound device. Differences in surface stiffness were observed between gender, activity level, and indentation location groups. The lower arm posterior location had the highest average stiffness (3.89 × 10 −3 MPa/mm), while the lowest stiffness was observed at the upper leg posterior location (0.98 × 10 −3 MPa/mm). The differences between indentation sites were larger in magnitude when compared to differences due to demographics (gender and activity level). However the large ranges of the 95% confidence intervals suggest that an aggregated metric based on population or sub-group may not capture individual variations. This study implicates the motivation to explore tissue composition variations within the indentation sites as well as the potential importance to include variations in surface stiffness during surgical simulations.